Pemetaan Wacana Syariah dan HAM dalam Penulisan Tesis Mahasiswa - Mansur, Mansur; Jahroh, Siti; Nasruloh, Mochamad Nadif (UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract: The existence of the study of sharia sciences in universities can be a barometer of how sharia sciences have been conceptually developed and have dynamically responded to developments and societal demands. That is why it is important to continue to pay close attention to the teaching and learning process of sharia sciences in higher education, for example through in-depth studies of trend maps of sharia discourse and human rights (human rights) in student thesis writing. The Sharia Science Master's Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta is one of the many study programs whose learning focuses on the study of sharia sciences. There are three academic problems that are the focus of this paper's study, namely (1) what discourses tend to be the tendencies of students in the Sharia Science Master's Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta in writing their theses from 2016 to 2020, (2) Is there any relevance of the choice of discourse tendencies in writing the student's thesis to the competence of the Master of Sharia Science Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta, and (3) is there a correlation between the understanding of scientific theory of students in the Master of Sharia Science Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta with the choice of discourse tendencies in writing their thesis, especially related to human rights discourse. The results of the search for student thesis data for 2016-2020, Master of Sharia Science Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta, show that the tendencies of sharia and human rights discourse in students' thesis writing vary greatly according to the scope of each concentration. There are, namely Islamic family law, sharia economic/business law, and constitutional law. However, there are still several theses studies that only repeat the themes of previous studies. In contrast to case studies and field studies, character studies still seem to be minimal in the trend of writing theses for students of the Master of Sharia Science Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta. In fact, studying figures and their thoughts in the field of sharia and human rights studies is very important for the development of sharia science itself. This is closely related to theoretical understanding related to the special skills aspects of students in the Master of Sharia Science Study Program, Faculty of Sharia and Law, UIN Sunan Kalijaga Yogyakarta, which still need to be improved in the future.Abstrak: Adanya kajian ilmu-ilmu syariah di perguruan tinggi dapat menjadi salah satu barometer tentang bagaimana ilmu-ilmu syariah itu secara konseptual telah dikembangkan dan secara dinamis telah merespon perkembangan dan tuntutan masyarakat. Itulah mengapa menjadi penting untuk terus mencermati proses pengajaran dan pembelajaran ilmu-ilmu syariah di perguruan tinggi, misalnya melalui kajian mendalam tentang peta kecenderungan wacana syariah dan HAM (hak asasi manusia) dalam penulisan tesis mahasiswa. Program Studi Magister Ilmu Syariah Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta merupakan salah satu dari sekian program studi yang fokus pembelajarannya seputar kajian ilmu-ilmu syariah. Ada tiga problem akademik yang menjadi fokus kajian tulisan ini, yakni (1) wacana-wacana apa saja yang menjadi kecenderungan mahasiswa Program Studi Magister Ilmu Syariah Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta dalam penulisan tesis mereka dari tahun 2016 hingga 2020, (2) adakah relevansi pilihan kecenderungan wacana dalam penulisan tesis mahasiswa tersebut dengan kompetensi Program Studi Magister Ilmu Syariah Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta, dan (3) adakah korelasi antara pemahaman teori keilmuan mahasiswa Program Studi Magister Ilmu Syariah Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta dengan pilihan kecenderungan wacana dalam penulisan tesis mereka khususnya terkait dengan wacana HAM. Hasil penelusuran terhadap data-data tesis mahasiswa tahun 2016-2020 Program Studi Magister Ilmu Syariah Fakukltas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta menunjukkan bahwa kecenderungan wacana syariah dan HAM yang ada dalam penulisan tesis mahasiswa tersebut sangat beragam sesuai dengan ruang lingkup masing-masing konsentrasi yang ada, yakni hukum keluarga Islam, hukum ekonomi/bisnis syariah, dan hukum tata negara. Namun demikian, masih ditemukannya beberapa kajian tesis yang hanya mengulang tema-tema kajian sebelumnya. Berbeda dengan studi kasus dan studi lapangan, kajian studi tokoh nampaknya masih minim dalam kecenderungan penulisan tesis mahasiswa Program Studi Magister Ilmu Syariah Fakukltas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta. Padahal, studi tokoh dan pemikirannya dalam bidang kajian syariah dan HAM sangatlah penting guna pengembangan ilmu-ilmu syariah itu sendiri. Hal ini terkait erat dengan pemahaman teoritik terkait dengan aspek ketrampilan khusus mahasiswa Program Studi Magister Ilmu Syariah Fakukltas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta yang masih perlu ditingkatkan kembali pada masa-masa ke depan.